Comparison between deep brain stimulation and magnetic resonance-guided focused ultrasound in the treatment of essential tremor: a systematic review and pooled analysis of functional outcomes. Issue 12 (14th October 2020) - Giordano, Martina; Caccavella, Valerio Maria; Zaed, Ismail; Foglia Manzillo, Livia; Montano, Nicola; Olivi, Alessandro; Polli, Filippo Maria
Abstract : The current gold standard surgical treatment for medication-resistant essential tremor (ET) is deep brain stimulation (DBS). However, recent advances in technologies have led to the development of incisionless techniques, such as magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy. The authors perform a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement to compare unilateral MRgFUS thalamotomy to unilateral and bilateral DBS in the treatment of ET in terms of tremor severity and quality of life improvement. PubMed, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials and SCOPUS databases were searched. 45 eligible articles, published between 1990 and 2019, were retrieved. 1202 patients were treated with DBS and 477 were treated with MRgFUS thalamotomy. Postoperative tremor improvement was greater following DBS than MRgFUS thalamotomy (p<0.001). A subgroup analysis was carried out stratifying by treatment laterality: bilateral DBS was significantly superior to both MRgFUS and unilateral DBS (p<0.001), but no significant difference was recorded between MRgFUS and unilateral DBS (p<0.198). Postoperative quality of life improvement was significantly greater following MRgFUS thalamotomy than DBS (p<0.001). Complications were differently distributed among the two groups (p<0.001). Persistent complications were significantly more common in the MRgFUS group (p=0.042). While bilateral DBS proves superior to unilateral MRgFUS thalamotomy in the treatment of ET, a subgroup analysis suggests that treatment laterality is the most significant determinant of tremor improvement, thus highlighting the importance of future investigations on bilateral staged MRgFUS thalamotomy.